FAKTOR-FAKTOR PENYEBAB KERUSAKAN DINI PADA PERKERASAN JALAN - Tjitjik Wasiah Suroso (Jurnal Jalan-Jembatan, 2008)
Early damage of pavement occurs when one of the factors does not meet specified requirements. Factors that cause pavement damage are quantity and quality of asphalt, numbers of passing in compaction, mixing and compaction temperature, etc. Therefore, research on pavement damage factors is required as early pavement damage occurred in many locations. The paper deals with the laboratory research results and the result of road improvement in several locations where early pavement damage occurred (less than a year). Research result shows that the causes of pavement damage are the lack of asphalt content (3.5 â€“ 5.3%) and inadequate compaction so that asphalt easily hardened (penetration value of asphalt 20) as a result of high void content and low asphalt content. Laboratory research indicated that when mix temperature is lower than temperature of viscosity 270 Â± 20cSt and low asphalt mix temperature will influence asphalt mix performance such as voids between aggregates are bigger, voids filled with asphalt are low. Those factors are also the causes of early damage. Keywords : Asphalt Content, Void Content, Asphalt Hardening